2‐Methoxy‐5((3, 4, 5‐trimethosyphenyl) seleninyl) phenol causes G2/M cell cycle arrest and apoptosis in NSCLC cells through mitochondrial apoptotic pathway and MDM2 inhibition. Issue 7 (5th April 2022) - Liu, Yang; Meng, Yuting; Bian, Jiang; Liu, Bolin; Li, Xuefen; Guan, Qi; Li, Zengqiang; Zhang, Weige; Wu, Yingliang; Zuo, Daiying
Abstract: Nonsmall cell lung cancer (NSCLC) is one of the most common malignancies and needs novel and effective chemotherapy. In this study, our purpose is to explore the anticancer effects of 2‐methoxy‐5((3, 4, 5‐trimethosyphenyl) seleninyl) phenol (SQ) on human NSCLC (A549 and H460) cells. We found that SQ suppressed the proliferation of NSCLC cells in time‐ and dose‐dependent manners, and blocked the cells at G2/M phase, which was relevant to microtubule depolymerization. Additionally, SQ induced A549 and H460 cell apoptosis by activating the mitochondrial apoptotic pathway. Further, we demonstrated that SQ enhanced the generation of reactive oxygen species (ROS), and pretreatment with N‐acetyl‐ L ‐cysteine (NAC) attenuated SQ‐induced cell apoptosis. Meanwhile, SQ mediated‐ROS generation caused DNA damage in A549 and H460 cells. Our data also revealed that SQ‐induced apoptosis was correlated with the inhibition of mouse double minute 2 (MDM2) in A549 and H460 cells. In summary, our research indicates that the novel compound SQ has great potential for therapeutic treatment of NSCLC in future.